2023
DOI: 10.3389/fvets.2023.1250251
|View full text |Cite
|
Sign up to set email alerts
|

Choice, control, and animal welfare: definitions and essential inquiries to advance animal welfare science

Abstract: The ways in which humans can support good welfare for animals in their care is an ongoing subject of debate: some place emphasis on the animals’ physical health; others, on animals’ ability to live “natural lives”; and others on animals’ affective states or psychological wellbeing. Recently, there has been an increase in interest in how an animal’s ability to exercise control over its environment could impact their welfare. In this article, we take the stance that the relevant aspects of the first two concepts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…While often used as if they are one word or concept (i.e., giving more choice and control = improved welfare) the terms are distinct. Choice is the animal’s ability to choose between multiple relatively salient behavioral options while control refers to an animal’s ability to produce desired results, such as producing an expected effect [ 12 ]. Individuals exercise control over the environment by making choices [ 13 ].…”
Section: Moving Toward a More Positive Futurementioning
confidence: 99%
See 3 more Smart Citations
“…While often used as if they are one word or concept (i.e., giving more choice and control = improved welfare) the terms are distinct. Choice is the animal’s ability to choose between multiple relatively salient behavioral options while control refers to an animal’s ability to produce desired results, such as producing an expected effect [ 12 ]. Individuals exercise control over the environment by making choices [ 13 ].…”
Section: Moving Toward a More Positive Futurementioning
confidence: 99%
“…When caregivers respond to these subtle signals in ways that make an animal more comfortable, as determined by its body language, they give the animal more choice, more control, and a vote in deciding what the caregiver should do in a particular situation. Having multiple opportunities to make choices and have more control over the contingencies in their lives gives animals a higher degree of freedom [ 31 ] and improved welfare [ 12 , 13 , 16 , 17 ].…”
Section: A Model For Improved Ambassador Animal Welfarementioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, the facility’s policy towards choice and control is evaluated. Recent advances in zoo animal research have demonstrated that affording animals the opportunities to choose between two or more possibilities—for example, staying in the inside or outside part of their enclosure—benefits their overall welfare [ 144 , 145 , 146 ]. To grant dolphins a degree of choice and control and to respond to individual preferences, they could, for example, be allowed to choose between different enrichment devices or types of positive reinforcement.…”
Section: Final Toolmentioning
confidence: 99%